2019
DOI: 10.1016/j.jallcom.2019.01.229
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation in an A356 foundry alloy with Cu additions - A transmission electron microscopy study

Abstract: The influence of different Cu addition levels on the age hardening and precipitation behaviors in an Al356 foundry alloy during artificial aging treatments has been systematically studied. A detailed characterization of the precipitates at the atomic scale has been done by using high angle annular dark field (HAADF) scanning transmission electron microscopy (STEM). At peak hardness, the number density of needle shape precipitates increases with increasing Cu content, while the dominant hardening precipitates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 50 publications
5
14
0
Order By: Relevance
“…In addition, the habit plane for Si precipitate is identified as {111} Si that is parallel to {010}Al, at which an OR can also be recognized with the adjacent Al matrix: {111}<01-1> Si // {010}<001> Al . The OR between Si and Al matrix is in agreement with the results reported by Mørtsell et al [27]. The third type of Si precipitates viewing along <111> Si is presented in Fig.…”
Section: Precipitatessupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the habit plane for Si precipitate is identified as {111} Si that is parallel to {010}Al, at which an OR can also be recognized with the adjacent Al matrix: {111}<01-1> Si // {010}<001> Al . The OR between Si and Al matrix is in agreement with the results reported by Mørtsell et al [27]. The third type of Si precipitates viewing along <111> Si is presented in Fig.…”
Section: Precipitatessupporting
confidence: 91%
“…For binary Al-Si alloy, it is reported that Si usually precipitate on {111} Al [29] which having an incoherent Si/Al interface. Whilst with elemental segregation on Si precipitate [27], it tends to precipitate on {010} Al leading to form a semi-coherence interface instead. The presence of segregation seems acting as a misfit reliever [30], and suppressing misfit dislocation at the interface [31].…”
Section: Segregation On Si Precipitatesmentioning
confidence: 99%
“…Regarding the influence of the addition of Cu on the silicon phase, previous literature has given various opinions on this: Mørtsell et al [29] found that the addition of 1.0 wt% Cu into A356 alloy decreased the Si size. The phenomenon was explained with quenching vacancies: Cu and Si both have a high affinity for vacancies, and the addition of a solute with high affinity for vacancies (Cu) in the matrix contributes to the precipitation of the silicon phase.…”
Section: Effect Of Cu-nps@gnps On Silicon Phasesmentioning
confidence: 99%
“…Furthermore, there is an increasing environmental threat that engine blocks pose to the environment. Engine blocks are not biodegradable and the use of organic biodegradable materials as reinforcements in A356 alloy composite has not been exploited [5,[10][11][12]. So, to what extent has the disposed engine blocks (i.e.…”
Section: Research Problem and Noveltymentioning
confidence: 99%